Gestión administrativa y su incidencia en el clima organizacional de la empresa nirsa s.a Posorja, año 2023 - Barzola Díaz, Luis Alberto (2025)
This project was carried out with the main objective of analyzing the impact of administrative management on the organizational climate of NIRSA S.A. Posorja, in 2023. The study has a mixed approach, in which quantitative and qualitative data were obtained with the help of methods such as inductive, deductive, and statistical. The research was documentary, field, and descriptive. The instruments used were an interview with the manager and a survey of 60 department heads and 366 plant employees. The results obtained evidenced solid yet rigid planning. The organization highlights resource optimization; management relies on transactional and transformational leadership, which drives innovation, productivity, and regulatory compliance; while control is efficient but requires constant supervision to minimize risks. The organizational climate diagnosis reflected strengths in communication, culture, working conditions, and training, promoting a safe and organized environment. However, weaknesses are evident in recognition, equity in rewards, and support for professional development, especially in the face of digitalization processes. There is a positive and significant relationship between administrative management and organizational climate, with Spearman's Rho coefficients of 0.903 and 0.923, and a high reliability of 99% according to Cronbach's Alpha. Therefore, it is proposed to implement flexibility strategies, strengthen recognition programs, and generate professional development opportunities that foster work efficiency and improve the work environment.